Plasma exchange in inflammatory demyelinating disorders of the central nervous system: reasonable use in the clinical practice - André Luiz Guimarães de Queiroz; Herval Ribeiro Soares Neto; Thiago Taya Kobayashi; Sonia Maria Cesar de Azevedo Silva (Arquivos de Neuro-Psiquiatria)
Plasma exchange (PLEX) is a therapeutic apheresis modality in which the plasma is separated from inflammatory factors such as circulating autoreactive immunoglobulins, the complement system, and cytokines, and its therapeutic effect is based on the removal of these mediators of pathological processes. Plasma exchange is well established for various neurological disorders, and it is applied successfully in central nervous system inflammatory demyelinating diseases (CNS-IDD). It mainly modulates the humoral immune system; thus, it has a greater theoretical effect in diseases with prominent humoral mechanisms, such as neuromyelitis optica (NMO). However, it also has a proven therapeutic effect in multiple sclerosis (MS) attacks. Several studies have suggested that patients with severe attacks of CNS-IDD have poor response to steroid therapy but show clinical improvement after the PLEX treatment. Currently, PLEX is generally established only as a rescue therapy for steroid unresponsive relapses. However, there are still research gaps in the literature regarding plasma volume, number of sessions, and how early the apheresis treatment needs to started. Thus, in the present article, we summarize the clinical studies and meta-analyses, especially about MS and NMO, outlining clinical data regarding the experience with therapeutic PLEX in severe attacks of CNS-IDD, the clinical improvement rates, the prognostic factors of a favorable response, and highlighting the likely role of the early apheresis treatment. Further, we have gathered this evidence and suggested a protocol for the treatment of CNS-IDD with PLEX in the routine clinical practice.